Rolling circle replication of DNA in yeast mitochondria. - Maleszka, R (1991)
The conformation of mitochondrial DNA (mtDNA) from yeasts has been examined by pulsed field gel electrophoresis and electron microscopy. The majority of mtDNA from Candida (Torulopsis) glabrata (mtDNA unit size, 19 kb) exists as linear molecules ranging in size from 50 to 150 kb or 2-7 genome units. A small proportion of mtDNA is present as supercoiled or relaxed circular molecules. Additional components, detected by electron microscopy, are circular molecules with either single- or double-stranded tails (lariats). The presence of lariats, together with the observation that the majority of mtDNA is linear and 2-7 genome units in length, suggests that replication occurs by a rolling circle mechanism. Replication of mtDNA in other yeasts is thought to occur by the same mechanism. For Saccharomyces cerevisiae, the majority of mtDNA is linear and of heterogeneous length. Furthermore, linear DNA is the chief component of a plasmid, pMK2, when it is located in the mitochondrion of baker's yeast, although only circular DNA is detected when this plasmid occurs in the nucleus. The implications of long linear mtDNA for hypotheses concerning the ploidy paradox and the mechanism of the petite mutation are discussed.